2014
DOI: 10.1177/1078345813518637
|View full text |Cite
|
Sign up to set email alerts
|

Surveillance of Suicidal and Nonsuicidal Self-Injury in the New York City Jail System

Abstract: Suicide and nonsuicidal self-injury represent significant causes of morbidity and mortality in jail settings. The New York City Department of Health and Mental Hygiene instituted a database of suicidal and nonsuicidal self-injuries in 2007. Between 2007 and 2011, there were eight deaths by suicide and 2,514 acts of self-injury, with the annual rate of self-injury increasing significantly throughout this time period. The most frequent methods of self-injury were lacerations (816), ligature tied around the neck … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…Regardless of the various types of self-harm behavior, for both sexes, the acts of cutting and scratching are the most common types (Hawton et al, 2014;Walsh, 2007). Additionally, the act of striking the head is becoming more frequent (Selling et al, 2014).…”
Section: Defining Self-harm In Prisonmentioning
confidence: 99%
“…Regardless of the various types of self-harm behavior, for both sexes, the acts of cutting and scratching are the most common types (Hawton et al, 2014;Walsh, 2007). Additionally, the act of striking the head is becoming more frequent (Selling et al, 2014).…”
Section: Defining Self-harm In Prisonmentioning
confidence: 99%
“… 5. Swallowing foreign objects (e.g., batteries, paper clips, pieces of metal, and pieces of razors) is fairly common in correctional settings (Kaba et al, 2014; Selling et al, 2014; Smith & Kaminski, 2011) and was identified by staff as sufficiently important to include on their tracking sheets. …”
mentioning
confidence: 99%